2009
DOI: 10.1556/oh.2009.28769
|View full text |Cite
|
Sign up to set email alerts
|

Liver support systems today

Abstract: Liver failure carries a high mortality, both the acute type with no pre-existing liver disease (acute liver failure) and the acute decompensation superimposed on a chronic liver disorder (acute on chronic liver failure). Today, liver transplantation still represents the only curative treatment for liver failure due to end-stage liver diseases. Donor organ shortage is still the major limitation and many patients die while awaiting transplantation. Due to the scarcity of donor organs, liver support technologies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…At present, the morbidity of RF is increasing all over the world, and it puts an increasingly serious threat to patients [ 17 , 18 ]. The treatment of RF patients is the top priority in clinical research, and the effect of HF-HD combined with systemic HP on RF has been preliminarily determined [ 19 , 20 ]. In order to further apply this treatment scheme clinically, this study evaluated the changes of GRP78 and miR-495-3p during HF-HD combined with systemic HP, which can provide more accurate reference for future clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the morbidity of RF is increasing all over the world, and it puts an increasingly serious threat to patients [ 17 , 18 ]. The treatment of RF patients is the top priority in clinical research, and the effect of HF-HD combined with systemic HP on RF has been preliminarily determined [ 19 , 20 ]. In order to further apply this treatment scheme clinically, this study evaluated the changes of GRP78 and miR-495-3p during HF-HD combined with systemic HP, which can provide more accurate reference for future clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Damaged proteins may be highly sensitive protein‐based biomarkers of oxidative processes in mammalian systems. Albumin, an important transport vehicle, was found to be severely oxidized in ACLF patients; these patients can thus benefit from artificial liver support systems via the removal of albumin‐bound toxins 29 . The report from China showed that plasma exchange, one of the artificial liver support systems, was found to significantly improve survival 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Challenges include selecting the sources of hepatocytes for the bioreactor; the stabilization of these primary hepatocytes in the bioreactor to maintain morphology, differentiation and function; and the design of the bioreactor, which requires adequate bidirectional mass transport, and cell viability to perform liver functions. Issues of safety with regard to infection and oncogenesis, as well as high cost are major concerns of these systems, which are considered as yet to be experimental [22].…”
Section: Mof Deathmentioning
confidence: 99%